2020
DOI: 10.1038/s41598-020-78395-y
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety evaluation of culture-expanded human chondrocytes with growth factor cocktail: a preclinical study

Abstract: The scarcity of chondrocytes is a major challenge for cartilage tissue engineering. Monolayer expansion is necessary to amplify the limited number of chondrocytes needed for clinical application. Growth factors are often added to improve monolayer culture conditions, promoting proliferation, and enhancing chondrogenesis. Limited knowledge on the biosafety of the cell products manipulated with growth factors in culture has driven this study to evaluate the impact of growth factor cocktail supplements in chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…These results are in accordance with the study by Khan et al [47], where a simultaneous increase in both proliferation and differentiation of ADSCs were obtained when VEGF-A165 was combined with FGF-2. In general, our results are in line with all studies, in which FGF-2 is used for expansion of various cell types, such as mesenchymal stem cells including ADSCs [17], induced pluripotent stem cells [19] or chondrocytes [18], or for various regenerative therapies, in which the cell proliferation is needed, such as healing of cutaneous wounds [20,21], regeneration of damaged or diseased bone tissue [22,24], or treatment of vitiligo, requiring proliferation of melanocytes [26].…”
Section: Number Of Cells In Media With Growth Factorssupporting
confidence: 86%
See 2 more Smart Citations
“…These results are in accordance with the study by Khan et al [47], where a simultaneous increase in both proliferation and differentiation of ADSCs were obtained when VEGF-A165 was combined with FGF-2. In general, our results are in line with all studies, in which FGF-2 is used for expansion of various cell types, such as mesenchymal stem cells including ADSCs [17], induced pluripotent stem cells [19] or chondrocytes [18], or for various regenerative therapies, in which the cell proliferation is needed, such as healing of cutaneous wounds [20,21], regeneration of damaged or diseased bone tissue [22,24], or treatment of vitiligo, requiring proliferation of melanocytes [26].…”
Section: Number Of Cells In Media With Growth Factorssupporting
confidence: 86%
“…However, the effect of our recombinant growth factors was tested on two cell types (with different results obtained for each cell type) and in a wide range of concentrations. These concentrations were inspired by the literature, where lower concentrations (5-100 ng/mL) have been usually used for studies with soluble growth factors (e.g., [2,12,15,[17][18][19]47,49]), while higher concentrations (0.5 -10 μg/mL) have been used for functionalization of various biomaterials (e.g., [12,14,15,33,34,36,37]) to simulate a local concentration of growth factors bound to the natural ECM in vivo, which can act as reservoirs of these factors, enabling their continuous release and delivery to cells [68].…”
Section: Limitation Of An In Vitro Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, large quantities of chondrocytes are needed for cartilage repair, which makes ex-vivo expansion essential for any potential use in ACI. When chondrocytes are expanded, they are cultured in a monolayer 2D culturing system, which is an effective method that generates a large number of viable cells [ 45 ]. Several commercial ACI expansion companies use two-dimensional monolayer systems to provide patients with 4 to 12 million viable cells for implantation ( Table 1 ).…”
Section: The Aci Proceduresmentioning
confidence: 99%
“…Multiple studies using nasal septum [65][66][67] and ear [68,69] cartilages showed that the constructs formed by these two cells sources survived subcutaneously even after six weeks [69] and six months [65] of implantation in nude mice. Unlike nasal septum and ear cartilages, articular cartilage lines the epiphyses of joint ends of the bone.…”
Section: Discussionmentioning
confidence: 99%